2014
DOI: 10.4236/ojms.2014.44031
|View full text |Cite
|
Sign up to set email alerts
|

Decline in Diversity and Production of Exploited Fishery Resources in Vembanad Wetland System: Strategies for Better Management and Conservation

Abstract: This paper describes the fishery catch structure of Vembanad wetland system during August 2012 to July 2013. The estimates of fishery production indicated an annual landing of 4387.31 t, in which 480.98 t and 3906.33 t contributed by southern and northern zone of Vembanad respectively. Eighty species of finfishes, five species of penaeid shrimps, three species of palaemonid prawns and two species of crabs were identified from the study period. The catch per unit effort (CPUE) value was maximum for gill net (3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Among the environmental parameters, variation in fish assemblage, composition and abundance in Vembanad estuarine system the depth, temperature, pH and salinity seemed to be the key factors [114]. Salinity acts as a prime factor influencing the distribution and abundance of organisms in estuaries and many dominant fish species in the pre barrage phase have become a rarity [27] and their distribution pattern was determined by salinity gradient prevailing in the estuary [26]. Anthropogenic activities along with increase in fishing pressure on estuarine systems affects the species threatening its very existence [115,116].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Among the environmental parameters, variation in fish assemblage, composition and abundance in Vembanad estuarine system the depth, temperature, pH and salinity seemed to be the key factors [114]. Salinity acts as a prime factor influencing the distribution and abundance of organisms in estuaries and many dominant fish species in the pre barrage phase have become a rarity [27] and their distribution pattern was determined by salinity gradient prevailing in the estuary [26]. Anthropogenic activities along with increase in fishing pressure on estuarine systems affects the species threatening its very existence [115,116].…”
Section: Discussionmentioning
confidence: 98%
“…Analysing the fishery of both sectors of the estuary, the southern stations noted a radical decline in annual landings from 500 t in 1988-1989 [24] to 486 t from 1995 -1999 [112], to a slight increase upto 507t during 2000-2001 [26] and further decline to 480.98t during 2012-2013 [27]. In the southern zone of Vembanad estuary, 67 species of finfishes and 14 species of shell fishes were recorded during 2008-2010 [113].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Stolephorus indicus and Sardinella gibbosa are both in the pelagic fish group on seagrass in the study area. Another study states that, Sardinella gibbosa is a pelagic fish that can be found in coastal waters dominated by mangrove and in turn contributes to regional offshore fisheries (Khatoon et al, 2014;Kumar et al, 2016;Swapna et al, 2016) and Stolephorus indicus is belonging pelagic-neritik and become the target of a small fishing catch (Asha et al, 2014). Consequently, the abundance of fish species diversity in seagrass beds highlights the importance of seagrass for these fish to survive and is an important factor to considered in conservation strategies for seagrass in the study area.…”
Section: The Abundance and Diversity Of Fish As Indicators Of Seagrasmentioning
confidence: 99%
“…According to Asha et al, (2014) in Vembanad lake gill net showed highest CPUE of 3.04 kg•h −1 followed by stake net having 2.43 kg•h −1 , Chinese dip net 2.01 kg•h −1 , seine net with 1.2 kg•h −1 , cast net with 0.72 kg•h −1 , hook and line with 0.34 kg•h −1 and traps with 0.26 kg•h −1 . The difference in the catch observed in the present study may be due to restricted study to few landing centers of the Vembanad Lake despite the former study covered a wider area.…”
Section: Catch Per Unit Effortmentioning
confidence: 99%